Feeling rules in the marriage equality movement: Public protest, social media and the management of emotion. (1st March 2021) - Crabtree, Arialle K.; Richards, Patricia
In recent years, scholars have turned their attention to the role of emotion on social networking sites. Much of this research has focused on social media as a space where emotions develop and are transformed in order for movement organizations to mobilize participants. This article uses activism around marriage equality in Georgia to explore participants' experiences of emotion during public protest events and on social media. Utilizing interviews, participant observation and content analysis, we identify the feeling and expression rules operating in these public spaces. We argue that each setting is associated with a unique emotional culture. Finally, we discuss strategies used by participants to manage emotions related to their activism in these various contexts. Our findings indicate that social media sites ‐ specifically Facebook and Twitter ‐ may act as a place where individuals negotiate emotions deemed inappropriate at public protests. This case demonstrates the importance of social context, including online venues, for understanding participants' experiences of emotion and activism.